2006
DOI: 10.1089/fpd.2006.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Subtyping: A Proposed PulseNet Protocol for Multiple-Locus Variable-Number Tandem Repeat Analysis of Shiga Toxin–ProducingEscherichia coliO157 (STEC O157)

Abstract: Most bacterial genomes contain tandem duplications of short DNA sequences, termed "variable-number tandem repeats" (VNTR). A subtyping method targeting these repeats, multiple-locus VNTR analysis (MLVA), has emerged as a powerful tool for characterization of clonal organisms such as Shiga toxin-producing Escherichia coli O157 (STEC O157). We modified and optimized a recently published MLVA scheme targeting 29 polymorphic VNTR regions of STEC O157 to render it suitable for routine use by public health laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
156
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 22 publications
8
156
2
Order By: Relevance
“…As reported previously, the discrimination power of MLVA is equal to, or even higher than, that of PFGE (3,4). In the present study, five MLVA profiles were found among seven strains with an identical PFGE pattern, demonstrating that MLVA can discriminate in great detail among epidemiologically unrelated strains with an identical PFGE type.…”
supporting
confidence: 83%
“…As reported previously, the discrimination power of MLVA is equal to, or even higher than, that of PFGE (3,4). In the present study, five MLVA profiles were found among seven strains with an identical PFGE pattern, demonstrating that MLVA can discriminate in great detail among epidemiologically unrelated strains with an identical PFGE type.…”
supporting
confidence: 83%
“…In spite of the universal implementation of PFGE as a subtyping method and as a foundation of the PulseNet, this technology suffers from some limitations (3,6,7,22).…”
mentioning
confidence: 99%
“…Using labeled primers with different dyes, it is possible to perform multiplex PCR followed by CGE-LIF to provide microbiological identification with less uncertainty than with AGE analysis. This methodology has proven to be a powerful tool for differentiating serovars of S. enterica and Shiga toxin-producing E. coli O157, and therefore, it may be a helpful tool in foodborne disease surveillance programs [74,75].…”
Section: Genome-based Methodsmentioning
confidence: 99%